2020
DOI: 10.3390/admsci10040093
|View full text |Cite
|
Sign up to set email alerts
|

Justice for the Crowd: Organizational Justice and Turnover in Crowd-Based Labor

Abstract: Crowd-based labor has been widely implemented to solve human resource shortages cost-effectively and creatively. However, while investigations into the benefits of crowd-based labor for organizations exist, our understanding of how crowd-based labor practices influence crowd-based worker justice perceptions and worker turnover is notably underdeveloped. To address this issue, we review the extant literature concerning crowd-based labor platforms and propose a conceptual model detailing the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 137 publications
(183 reference statements)
0
5
0
Order By: Relevance
“…Airbnb's case highlights the importance of organizational justice, a concept concerning employee perceptions of fairness in the workplace [47,48]. Previous research has shown that fairness is crucial for several reasons [48][49][50][51]. Firstly, fair decision implementation by supervisors leads to greater organizational commitment and improved performance among employees (e.g., [52]).…”
Section: Organizational Justice and Surviving Employeesmentioning
confidence: 99%
“…Airbnb's case highlights the importance of organizational justice, a concept concerning employee perceptions of fairness in the workplace [47,48]. Previous research has shown that fairness is crucial for several reasons [48][49][50][51]. Firstly, fair decision implementation by supervisors leads to greater organizational commitment and improved performance among employees (e.g., [52]).…”
Section: Organizational Justice and Surviving Employeesmentioning
confidence: 99%
“…The principle of distributive justice (DJ) relates to the fairness of resource and reward allocation decisions within an entity (Greenberg, 1990;Song et al, 2020). Employees are more likely to remain with an organisation when they see how the organisation distributes its resources, such as benefits, payments, and duties, equally among employees (Mengstie, 2020).…”
Section: Distributive Justice (Dj) and Intention To Stay (Its)mentioning
confidence: 99%
“…Further, this means that, workplaces and an increasing awareness that the working standards in the firms may no longer reflect best practice, and it may no longer be necessary to classify employees. The findings of a number of commonly investigated attitudes and perceptions have been inconsistent, and important moderators have been identified Longley, 2020;Odendaal, 2000;Rahman & Valentine, 2021;Song et al, 2020).…”
Section: Theoretical Implicationsmentioning
confidence: 99%